The Shifting Prominence of Emotions in the Moral Philosophy of Thomas Aquinas (Diametros, 2013)
In this article, I claim that emotions, as we understand the term today, have a more prominent role in the moral life described by Thomas Aquinas than has been traditionally thought. First, clarity is needed about what exactly the emotions are in Aquinas. Second, clarity is needed about true virtue: specifically, about the relationship of acquired virtue to infused, supernatural virtues. Given a fuller understanding of both these things, I claim that emotions are not only auxiliary to the life of flourishing, specifically with regard to moral motivation and morally relevant knowledge. In fact, at the highest stage of moral development, emotions have a more prominent role than at lower stages. Pointing this out helps us to resist over-intellectualizing interpretations of Aquinas’s moral philosophy.
Keywords: Thomas Aquinas; emotion; passions; virtue; empathy; second-personal knowledge; theological virtues; Gifts of the Holy Spirit; moral motivation; moral knowledge